2018
DOI: 10.15560/14.6.961
|View full text |Cite
|
Sign up to set email alerts
|

First record of African Hind, Cephalopholis taeniops (Valenciennes, 1828) (Perciformes, Epinephelidae) in the South-western Atlantic

Abstract: Recent studies reported the introduction of non-native species on the Brazilian coast. In this contribution, we provide the first record of Cephalopholis taeniops (Valenciennes 1828) in the western South Atlantic, based on a specimen captured off the Ilhas Cagarras, Rio de Janeiro, Brazil, and discuss the potential agents for its introduction. While this single specimen was collected in 2006 in a well-known locality, no other specimen has been captured since.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Approval for the research protocol, granted by the Institutional Animal Care and Use Committee (IACUC) under the code PKNUIACUC-2022-72 on 15 December 2022, confirms that the use of biological material in the experiments adhered to ethical standards, ensuring that the targeted fish were not subjected to harm by the researchers. The range distribution of C. taeniops is mapped according to the IUCN data (.shp files) and the additional records published in the previous literature [7,[10][11][12][13][14][15][16] (Figure 1).…”
Section: Sampling and Species Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Approval for the research protocol, granted by the Institutional Animal Care and Use Committee (IACUC) under the code PKNUIACUC-2022-72 on 15 December 2022, confirms that the use of biological material in the experiments adhered to ethical standards, ensuring that the targeted fish were not subjected to harm by the researchers. The range distribution of C. taeniops is mapped according to the IUCN data (.shp files) and the additional records published in the previous literature [7,[10][11][12][13][14][15][16] (Figure 1).…”
Section: Sampling and Species Identificationmentioning
confidence: 99%
“…The African hind or blue-spotted seabass, Cephalopholis taeniops, inhabits sandy or rocky seafloors at depths ranging from 20 to 200 m in the Eastern Atlantic, spanning from Morocco south to Angola, including the Canary Islands (Spain), Cape Verde Islands, and São Tomé and Principe [7]. Subsequently, this species has been documented in the Canary Islands, the Mediterranean Sea in Libya and Israel, as well as in the Southwestern Atlantic Ocean [10][11][12][13][14][15][16]. Beyond the Eastern Atlantic, populations in the Mediterranean and Southwestern Atlantic are considered introduced populations of C. taeniops [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another specimen, housed in the Museu Nacional do Rio de Janeiro, MNRJ 16575, collected on October 10, 1997, at Praia dos Cabri-tos, Trindade Island, Espírito Santo, was examined by Lucas Canes Garcia when preparing the manuscript concerning Cephalopholis taeniops (Garcia et al, 2018). It was reidentified as an immature specimen of Epinephelus adscensionis (Osbeck, 1765), a very common species on Trindade Island and that might resemble Cephalopholis cruentata due to the numerous dark dots of head and body (Figure 5, C, D).…”
Section: Specimens Ofmentioning
confidence: 99%
“…taeniops (Valenciennes, 1828), the first two occurring only in the Western Atlantic, the others in the eastern and central areas of this ocean (Parenti & Randall, 2020). A confirmed record of C. taeniops from Brazil is regarded as an incidental transport from the Eastern Atlantic, possibly through an oil platform (Garcia et al, 2018); this species was erroneously reported by Steindachner (in Jordan & Evermann, 1896) as a stray to Florida and the Bahamas but is otherwise considered to be restricted to West Africa (Heemstra, 1991, Rocha, 2018.…”
Section: Introductionmentioning
confidence: 99%